Sociodemographic Characteristics of Gay and Lesbian Victims of Intimate Partner Psychological Abuse in Spain and Latin America / Características Sociodemográficas de Gais y Lesbianas Víctimas de Abuso Psicológico en Pareja en España E Hispanoamérica - Barrientos-Delgado, J (Routledge, 2018)
Psychological abuse in same-sex couples has hardly been studied in Spain and Latin America, despite its importance in society and public health. The objective of this study is to examine the prevalence of psychological abuse in same-sex couples in Spain and Latin America and analyse the associated sociodemographic characteristics. An online survey was conducted with 663 gay and lesbian respondents from Spain and Latin America. Of the total sample, 10.6% reported that they perceived themselves as victims of psychological abuse from their partner (9.6% in gay men and 10.7% in lesbians). In gay men, differences were found between victims and non-victims on the sociodemographic variables of age, professional status, and daily alcohol consumption. In lesbians, significant differences were found between victims and non-victims in the country and professional status variables. When comparing gay and lesbian victims, significant differences were found in professional status and alcohol consumption. This study contributes to better understanding of this phenomenon, and it reveals the need for further research. © 2018 Fundacion Infancia y Aprendizaje.